THE EFFECTS OF INQUIRY TRAINING MODEL USING MIND MAPPING AND MOTIVATION ON STUDENTS’ SCIENCE PROCESS SKILLS PHYSICS. - Dara Fitrah Dwi; Mara Bangun Harahap; Derlina . (Universitas Negeri Medan, 2016)
This study aims to analyze, student’s science process skills who are taught by inquiry training learning model using mind mapping is better than the students that taught with conventional learning, science process skills in students who have motivated above average are better compared with students who have the motivation below average, and the interaction between the inquiry training learning model using mind mapping and motivation in improving students' science process skills. This research was conducted by quasiexperimental. The sample selection was done by cluster random sampling that were class X2 and X1. The research instrument was using science process skills test in the form of descriptions and tests of motivation in the form of a questionnaire. The data were analyzed by ANOVA two lanes. The results showed that: The ability of students’ physics science process skills using inquiry training learning using mind mapping is better than the ability of students’ science process skills using conventional learning model. The ability of students’ physics science process skills in motivational groups are above average better than the ability of students’ physics science process skills in conventional groups which are below average, and In this research, motivation above average dominant improves science process skills in Inquiry Training model using mind mapping rather than in conventional learning model